Co-assembly of Janus nanoparticles in block copolymer systems. Issue 31 (18th July 2019) - Diaz, Javier; Pinna, Marco; Zvelindovsky, Andrei; Pagonabarraga, Ignacio
Abstract : Janus nanoparticles are mixed with block copolymer melts to produce highly ordered co-assembled structures of colloids within minority domains. Abstract : Block copolymer are ideal matrices to control the localisation of colloids. Furthermore, anisotropic nanoparticles such as Janus nanoparticles possess an additional orientational degree of freedom that can play a crucial role in the formation of highly ordered materials made of block copolymers. This work presents a mesoscopic simulation method to assert the co-assembly of Janus nanoparticles in a block copolymer mixture, finding numerous instances of aggregation and formation of ordered configurations. Comparison with chemically homogeneous neutral nanoparticles shows that Janus nanoparticles are less prone to induce bridging along lamellar domains, thus being a less destructive way to segregate nanoparticles at interfaces. The combination of asymmetric block copolymer and asymmetric Janus nanoparticles can result in assembly of colloids with an even number of layers within the minority domain.